A Curious Case of Intussusception. Issue 4 (July 2016) - Crawford, Todd C.; Allison, Derek B.; Kilic, Arman; Schwartz, Diane A.
Abstract : Abstract: Intestinal intussusception, although common in the pediatric population, is a rare problem in adults. Although asymptomatic transient episodes of intussusception may be seen on computed tomography because of technological advances, they are rarely of clinical significance. When symptomatic in adults or when observed in association with a tumor, this problem becomes pathologic, and surgical intervention is required. This case report describes a young adult male with symptomatic intussusception arising from a small bowel tumor. Surgical intervention led to a diagnosis of heterotopic pancreas serving as a lead point for an ileoileal intussusception. Both diagnostic and therapeutic, surgical resection of the intussusception also was found to be potentially preventive for the development of pancreatic cancer, as the heterotopic pancreatic tissue contained premalignant histological changes.